2022
DOI: 10.21203/rs.3.rs-1439005/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Profiling of a Prognostic RNA-Binding Protein Signature in Esophageal Cancer

Abstract: Background the roles of RNA-binding proteins (RBPs) in esophageal cancer (EC) need elucidation. Materials and methods The gene expression profiles and clinical data of patients with EC were downloaded from the Xena database. Candidate genes were obtained by taking the union of RBP genes, KEGG pathway-related genes and differentially expressed RBP genes from cluster analysis. Hub genes were extracted by PPI network construction. Result We built a Cox proportional hazards regression model with 7 prognostic RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A previous report showed that a de novo variant in the human HIST1H4J gene causes a syndrome analogous to HIST1H4C-associated neurodevelopmental disorder (66). Furthermore, HIST1H4J is the strongest negative predictor of ovarian cancer (67) and an important prognostic and chemoresistance predictor of ESCA (68). Herein, upregulation expression of HIST1H4J (log 2 FC =1.39; q value =1.87×10 −3 ) was observed in patients with ESCA.…”
Section: Discussionmentioning
confidence: 73%
“…A previous report showed that a de novo variant in the human HIST1H4J gene causes a syndrome analogous to HIST1H4C-associated neurodevelopmental disorder (66). Furthermore, HIST1H4J is the strongest negative predictor of ovarian cancer (67) and an important prognostic and chemoresistance predictor of ESCA (68). Herein, upregulation expression of HIST1H4J (log 2 FC =1.39; q value =1.87×10 −3 ) was observed in patients with ESCA.…”
Section: Discussionmentioning
confidence: 73%